Cryo‐EM for Small Molecules. Issue 12 (13th December 2022) - Cabral, Angela; Cabral, Julia Elise; McNulty, Reginald
Abstract: In recent years, protein structure analysis using cryo‐electron microscopy(cryo‐EM) has expanded and improved. In this review, we discuss many recent improvements to the field, the problems those improvements hope to solve, and some of the still unanswered questions. Most notably, this review will discuss improvements in resolving small or fragmented protein structures, as well as methods to improve the signal‐to‐noise ratio of the data by increasing image contrast using carbon‐based systems. We will also describe how, in the last 5 years, methodological improvements have allowed for better 3D image resolution by capturing a continuum of 3D images. We will provide examples of these methods in practice and discuss how these improved methods may be used in small‐molecule drug discovery and development. © 2022 Wiley Periodicals LLC.